SEVERAL INFLUENCES OF SYSTEM INFORMATION QUALITY TO USER SATISFACTION AND ITS IMPLICATION ON INDIVIDUAL PERFORMANCE - Sri Anjarwati; Apollo Apollo (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2019)
Research aimed to analyze several influences of system quality, information quality and perceived usefulness to user satisfaction on financial accounting software and its impact on individual performance. Sampling technique was using purposive sampling based on questionnaires distributed to users of financial accounting software who work at international freight forwarding. The number of samples was 200 respondents. The analytical method used was Structure Equation Models (SEM) with Lisrel 8.75 full version. The result of study showed that system quality and information quality have significant influenced the perceived usefulness. System quality, information quality, and perceived usefulness have significant influenced to user satisfaction. User satisfaction had significant influenced to individual performance. The highest influence from overall model was shown by the influence of system quality on perceived usefulness.